A Novel Rat Model to Simulate Positive Margins in the Wound Bed of a Resected Sarcoma - Gurtej Singh, PhD; Omer Kaymakcalan, MD; Thomas R. Hays, MD; Adam Abbas, BS; Sruthi Sridevan, MS; Jasleen Kaur, BS; Sourish Rathi, BS; Jocellie Marquez, MD; Soosan Ghazizadeh, PhD; Felix Tavernier, MD; Brendan F. Boyce, MD; Sami U. Khan, MD; et al. (Plastic and Reconstructive Surgery, Global Open)
Background:. One reason for local recurrence is the presence of positive surgical margins after tumor resection. An animal model accurately representing the microtumor burden will improve our understanding of these surgical margins. Using a rat model, we report a new methodology for creating microscopic tumors. Methods:. Four different cell densities (1000, 10,000, 100,000, and 500,000 cells) of virus-induced Rous sarcoma XC cells (ATCC CCL-165) were topically added to 1.0 cm × 1.0 cm full-thickness wounds of male Rowett nude rats. Both Tegaderm and Tensoplast were then used to dress the wounds. After 9 days, the wound beds were excised, stained with hematoxylin and eosin, and analyzed using National Institutes of Health Image J software. Results:. Better healing of the wound beds was observed for the smaller 2 cell densities (1000 and 10,000) as opposed to the higher 2 densities (100,000 and 500,000). The 2 higher cell density groups had gross identifiable tumors that extended deep through the dermis. On the other hand, the smaller cell density groups had microscopic tumor masses. Inflammation was present in all groups irrespective of the initial tumor cell densities, whereas hemorrhage was present only in the 2 higher cell density groups. Conclusions:. This methodology can create a clinically relevant scenario of positive surgical margins after tumor resection. This induction method is simple, reasonably quick to use, and requires minimal surgical expertise. This approach could also develop microscopically positive margins for a much more comprehensive array of cancers.